Lower Extremity Peripheral Arterial Disease Is an Independent Predictor of Coronary Heart Disease and Stroke Risks in Patients with Type 2 Diabetes Mellitus in China - Xiao-Hong Pang; Jue Han; Wan-Lan Ye; Xue Sun; Yue Ding; Wen-Juan Huang; Yi-Ming Zhao; Han-Yu Lou; Li-Zhen Shan; Ying-Xiu Kang; Xiao-Xiao Song; Song-Zhao Zhang; et al. (International Journal of Endocrinology)
We aimed to determine the relationship between lower extremity peripheral arterial disease (PAD), 10-year coronary heart disease (CHD), and stroke risks in patients with type 2 diabetes (T2DM) using the UKPDS risk engine. We enrolled 1178 hospitalized T2DM patients. The patients were divided into a lower extremity PAD group (ankle-brachial index≤0.9 or >1.4; 88 patients, 7.5%) and a non-PAD group (ankle-brachial index>0.9 and ≤1.4; 1090 patients, 92.5%). Age; duration of diabetes; systolic blood pressure; the hypertension rate; the use of hypertension drugs, ACEI /ARB, and statins; CHD risk; fatal CHD risk; stroke risk; and fatal stroke risk were significantly higher in the PAD group than in the non-PAD group (P<0.05 for all). Logistic stepwise regression analysis indicated that ABI was an independent predictor of 10-year CHD and stroke risks in T2DM patients. Compared with those in the T2DM non-PAD group, the odds ratios (ORs) for CHD and stroke risk were 3.6 (95% confidence interval (CI), 2.2–6.0; P<0.001) and 6.9 (95% CI, 4.0–11.8; P<0.001) in those with lower extremity PAD, respectively. In conclusion, lower extremity PAD increased coronary heart disease and stroke risks in T2DM.